2021
DOI: 10.18502/ijaai.v20i3.6333
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of Human Platelet Antigen-1 to -5 and -15 by Polymerase Chain Reaction with Sequence-specific Primers (PCR-SSP) and Real-time PCR in Azeri Blood Donors

Abstract: Human platelet antigens (HPAs) are glycoproteins on the platelet surface that a single nucleotide mutation in the coding region gene could lead to the variation of different HPA polymorphisms. These antigens have shown variation among different races and may trigger immune responses during blood transfusion and pregnancy. Genotyping of HPAs is useful for managing these reactions and establishing a platelet registry to decrease platelet transfusion reactions. This study aimed to compare allelic and genotype fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Considering that the frequency of HPAs polymorphisms regardless of the ethnicity has been studied in Iran so far,[ 3 5 7 10 ] the existence of such differences in the frequency of platelet antigen systems in the present study (Turkmen ethnicity) with other studies in the country can be attributed to racial differences that need further investigation in this regard.…”
Section: Discussionmentioning
confidence: 70%
“…Considering that the frequency of HPAs polymorphisms regardless of the ethnicity has been studied in Iran so far,[ 3 5 7 10 ] the existence of such differences in the frequency of platelet antigen systems in the present study (Turkmen ethnicity) with other studies in the country can be attributed to racial differences that need further investigation in this regard.…”
Section: Discussionmentioning
confidence: 70%
“…Therefore, only HLA-A and HLA-B loci were routinely analyzed to search for HLA-matched/compatible platelet units ( 20 ). The HPA genotyping methods included PCR-SSP, TaqMan assay, PCR-SBT, and NGS ( 22 , 23 , 33 , 34 ). However, there is a rare study for HPA and HLA genotyping simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…In order to genotype for HLA-typed and/or HPA-typed unrelated donors, it needs to provide the corresponding methods for HLA-A and HLA-B loci, and HPA systems. Currently, many methods have been developed to detect HLA-A and HLA-B loci and HPA systems, including PCR sequence-specific primers (PCR-SSP), PCR sequence-based typing (PCR-SBT), and real-time PCR ( 11 , 21 23 ). However, these methods always detect single gene separately and need too many wells and multiple amplification for the test.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a large diversity of HPA genotypes have been reported from varied human ethnic groups from a variety of geographical locations (Azizi et al., 2021; Hayashi et al., 2020; Jovanovic Srzentic et al., 2021; Kazemi et al., 2020; Silva‐Malta et al., 2018; Yan et al., 2006). Many of these studies have suggested significant differences in the frequencies between populations.…”
Section: Introductionmentioning
confidence: 99%